Changes in glucose tolerance after endoscopic retrograde cholangiopancreatography. Issue 7 (July 1981) - Tulassay, Z; Papp, J; Szathmári, M; Kisfaludy, S; Korányi, L; Tamás, G
Abstract : Changes in oral glucose-tolerance have been studied in patients subjected to endoscopic retrograde pancreatography. Glucose tolerance is impaired 72 hours after ductography, and significant changes can still be seen even after one month; glucose tolerance returns to normal six to 12 months after pancreatography. In an attempt to discover the mechanism underlying impaired tolerance serial measurements were made of plasma insulin and glucagon levels. The observation that the ratio I/G decreased in these patients indicates that enhanced glucagon release, probably due to mechanical and/or osmotic injury, may be responsible for the hyperglycaemia that is observed.